Cold isospin asymmetric baryonic rich matter in nonlocal NJL-like models - Carlomagno, Juan Pablo (2024)
We study the features of low energy strong interactions for a system at zero temperature and finite baryon and isospin chemical potentials, in the framework of aNambu–Jona-Lasinio-like model that includes nonlocal four-point interactions. Weanalyze the phase transitions corresponding to chiral symmetry restoration and pioncondensation, comparing our results with those obtained from local NJL-like modelsand lattice QCD calculations.